ANALISIS PENGARUH SUMBER DAYA MANUSIA, UPAH, KEPUASAN, LINGKUNGAN KERJA, DISIPLIN DAN MOTIVASI TERHADAP KINERJA PETUGAS PARKIR DI KOTA BOYOLALI - Ismail, Edi Muh; Sunarto, St; Budiyono, Rokhmad; Novandalina, Arini (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
This study aims to determine the influence of human resources, wages, job satisfaction, work environment, discipline, and motivation on the performance of parking attendants in Boyolali City. The research population includes all parking attendants in Boyolali, totaling 150 individuals, with a sample of 60 respondents calculated using the Slovin formula and proportional cluster random sampling technique. The research approach is quantitative, with data collected through observation, questionnaires, and documentation. Data analysis employs multiple linear regression. The results indicate that the variables of human resources, wages, satisfaction, work environment, and motivation partially have a positive and significant effect on the performance of parking attendants, with the t-count values greater than the t-table values and Sig values < 0.05. However, discipline does not have a significant effect on performance, as indicated by a t-count value of 0.268 < t-table value of 2.000575 and a Sig value of 0.127 > 0.05. Simultaneously, these variables have a positive and significant effect on the performance of parking attendants in Boyolali, with an F-count value of 9.302 greater than the F-table value of 2.28 and a Sig value of 0.00 < 0.05. The study also found that the recruitment procedures for parking attendants in Boyolali City are unclear, thus it is recommended that the leadership provides clarity in the recruitment procedures to streamline the process